Analytical Study of the Economic Role of the Public and Private sectors in Investment and Employment in Syria (Journal of Hama University, 2019)
The aim of this study is to conduct an academic and objective comparison between the public and privet sectors' contributions in creating job opportunities (employment) and investment. These comparisons employed government statistics. In general, the study found that public and private sectors in Syria are not competing but complementing each other in the fields of employment and investment. In details, public sector creates job opportunities mainly in the field of services, and it depends on relatively more educated labor force. With regards to the private sector, it relies more on less educated but more evenly distributed labor force compared with the public sector. Privet sector's investments target first finance and insurance sector, then trade sector followed by building and construction sector. These results assure that economic plans aiming at encouraging investment and/or reducing unemployment in Syria should acknowledge the complement relationship between public and private sectors in order to be successful in achieving their goals.